A niobium-bismuth-based high-entropy alloy modified electrode for vanadium battery and preparation method thereof

Through the modified electrode of bismuth-based high-entropy alloy, the graphite felt electrode has been solved, and the problems of low electrochemical activity and poor conductivity in vanadium batteries are improved, the energy efficiency and Coulomb efficiency of vanadium batteries are suppressed, and the side reaction of hydrogen evolution is improved, and the electrode is improved. conductivity and dielectric properties.

CN118888768BActive Publication Date: 2025-01-07HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411354638.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing graphite felt electrodes have problems such as low electrochemical activity, many side reactions and poor conductivity in vanadium batteries, which affect the battery performance.

Method used

Using a modified electrode of bismuth-based high-entropy alloy, the niobium bismuth-based multi-metal oxide coupling and high-entropy alloy are formed by mixing niobium sources, bismuth-based sources, etc. with graphite felt and microwave heat treatment and high-temperature heat treatment to form a bismuth-based multi-metal oxide coupling and a high-entropy alloy to improve the conductivity of the electrode. and reactive activity.

Benefits of technology

The energy efficiency and Coulomb efficiency of vanadium batteries are improved, the side reaction of hydrogen evolution of the negative electrode is suppressed, the conductivity and dielectric properties of the electrode are improved, and the overall performance of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118888768B_ABST
    Figure CN118888768B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of all-vanadium liquid flow battery, and discloses a method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for vanadium battery, which comprises at least the following steps: dissolving a plurality of metal sources in an organic solution containing a surfactant and a metal chelating agent in a certain proportion to obtain a mixed solution; soaking graphite felt in the mixed solution, and then reacting the mixed solution and the graphite felt together under microwave heat treatment, and washing, drying and high-temperature heat treatment the graphite felt obtained by the reaction to obtain a niobium-bismuth-based high-entropy alloy modified electrode. The bismuth substrate in the high-entropy alloy modified electrode prepared by the present invention is conducive to inhibiting the hydrogen evolution reaction occurring on the negative electrode, and the niobium substrate provides more active sites for the valence change of vanadium on the anode, and the addition of a plurality of other metals can also reduce the electrode resistance, improve the conductivity of the electrode, and improve the voltage efficiency and energy efficiency, and has good application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of all-vanadium liquid flow battery electrodes, and specifically relates to a niobium-bismuth-based high-entropy alloy electrode for a vanadium battery and a preparation method thereof. Background Art

[0002] The all-vanadium liquid flow battery stack is mainly composed of electrodes, proton exchange membranes, plates and current collectors. The electrodes serve as the main reaction carriers, providing reaction sites for active substances, and their characteristics directly affect the performance of the battery. At present, carbon electrodes including graphite felt have attracted widespread attention due to their good corrosion resistance and large electrochemical area. However, they also have defects such as low electrochemical activity, side reactions, and poor conductivity when used as vanadium battery electrodes, and further modification is still needed to optimize their performance.

[0003] As a special multi-element alloy material, high entropy alloy has a highly uniform composition and crystal structure, providing more active sites for chemical reactions. Niobium metal plays a key role in liquid flow batteries, which is conducive to the change of valence state of vanadium at the anode, providing it with more active sites, while bismuth is conducive to inhibiting the hydrogen evolution reaction at the negative electrode. The high entropy alloy formed by introducing multiple conductive metals is conducive to enhancing the conductivity of the electrode. Summary of the invention

[0004] The purpose of the present invention is to provide a niobium-bismuth-based high-entropy alloy modified electrode for vanadium batteries and a preparation method thereof, so as to solve the problems of poor activity, side reaction and poor conductivity of existing graphite felt electrodes.

[0005] The technical solutions adopted are as follows:

[0006] Step S1: dissolving a niobium source, a bismuth source, a cobalt source, a manganese source, a nickel source, a vanadium source, a tungsten source, a surfactant and a metal chelating agent in an organic solvent to obtain a mixed solution;

[0007] Step S2: soaking 2-6 parts by mass of graphite felt in 300-600 parts by mass of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment. After the treatment, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out, and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material;

[0008] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under the protection of an inert gas, and naturally cooling it to room temperature to obtain a niobium-bismuth-based high-entropy alloy modified electrode.

[0009] Preferably, in step S1, the niobium source is one of niobium carbide, niobium oxalate and niobium chloride; the bismuth source is one of bismuth sulfate, bismuth 2-ethylhexanoate, bismuth subsalicylate and bismuth nitrate; the cobalt source is one of cobalt acetate, cobalt oxalate, cobalt nitrate and cobalt gluconate; the manganese source is one of manganese carbonate, manganese nitrate, manganese citrate and manganese cyclohexaneate; the nickel source is one of nickel chloride, nickel 2-ethylhexanoate and nickel citrate hydrate; the vanadium source is one of ammonium metavanadate, vanadium acetylacetonate, vanadium sulfate hydrate and vanadium phthalocyanine; the tungsten source is one of ammonium tungstate, tungsten hexacarbonyl and tungsten isopropoxide.

[0010] Preferably, in step S1, the molar concentrations of the niobium source, bismuth source, cobalt source, manganese source, nickel source, vanadium source and tungsten source in the mixed solution are 50-80mmol / L, 40-100mmol / L, 10-25mmol / L, 15-40mmol / L, 10-20mmol / L, 5-15mmol / L and 20-50mmol / L, respectively.

[0011] Preferably, the surfactant in step S1 is one of polyvinyl pyrrolidone, polysorbate, cetyltrimethylammonium bromide and hexamethylenetetramine, and the mass concentration in the mixed solution is 2-15 g / L.

[0012] Preferably, in step S1, the metal chelating agent is one of ethylenediaminetetraacetic acid, disodium nitrilotriacetate, citric acid, gluconic acid and sodium tripolyphosphate, and the molar concentration in the mixed solution is 5-35 mmol / L.

[0013] Preferably, the organic solvent in step S1 is one of ethylene glycol, n-propanol, glycerol and isoamyl alcohol.

[0014] Preferably, in step S2, the microwave heat treatment power setting range is 100-500W, the microwave heat treatment temperature is 150-200°C, and the microwave heat treatment time is 20-80min.

[0015] Preferably, in step S3, the high temperature heat treatment temperature is 800-1100° C., the high temperature heat treatment time is 2-6 hours, and the inert gas is one of nitrogen, argon and helium.

[0016] A niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery is prepared by using the above-mentioned method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery.

[0017] The beneficial effects of the present invention include at least:

[0018] 1. The present invention uses niobium and bismuth metals as the core to construct a multi-element high-entropy alloy with a highly uniform composition and lattice structure, wherein the niobium element can accelerate the valence state transformation of vanadium ions in vanadium batteries, enhance the related reaction activity, and thus enhance the energy efficiency of the battery;

[0019] 2. The addition of bismuth element in the niobium-bismuth-based high-entropy alloy modified electrode prepared by the present invention can effectively inhibit the occurrence of hydrogen evolution side reaction at the negative electrode of the vanadium battery, improve the charge and discharge performance, and thus improve the coulomb efficiency and energy efficiency of the battery;

[0020] 3. In the preparation process of niobium-bismuth-based high-entropy alloy modified electrodes, metal chelating agents can promote the uniformity and dispersion of multi-element distribution, and the addition of Co, Mn, W, Ni, and V metals can effectively improve the dielectric properties and conductivity of the electrodes, and improve voltage efficiency and energy efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of a method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery of the present invention;

[0022] Figure 2 Element distribution diagram of the niobium-bismuth-based high entropy alloy modified electrode prepared in Example 1;

[0023] Figure 3 Energy efficiency curves of batteries assembled with electrodes prepared in Example 1 and Comparative Example 5 after 20 cycles. DETAILED DESCRIPTION

[0024] See also Figure 1 A method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery comprises the following steps:

[0025] Step S1: dissolving a niobium source, a bismuth source, a cobalt source, a manganese source, a nickel source, a vanadium source, a tungsten source, a surfactant and a metal chelating agent in an organic solvent to obtain a mixed solution; the niobium source is one of niobium carbide, niobium oxalate and niobium chloride; the bismuth source is one of bismuth sulfate, bismuth 2-ethylhexanoate, bismuth subsalicylate and bismuth nitrate; the cobalt source is one of cobalt acetate, cobalt oxalate, cobalt nitrate and cobalt gluconate; the manganese source is one of manganese carbonate, manganese nitrate, manganese citrate and manganese cyclohexaneate; the nickel source is one of nickel chloride, nickel 2-ethylhexanoate and nickel citrate hydrate; the vanadium source is one of ammonium metavanadate, vanadium acetylacetonate, vanadium sulfate hydrate and vanadium phthalocyanine; the tungsten source is one of ammonium tungstate, hexacarbonyl tungsten and isopropoxide tungsten; the niobium source, bismuth source, cobalt source, manganese source, nickel source, vanadium source, The molar concentration of the tungsten source in the mixed solution is 50-80mmol / L, 40-100mmol / L, 10-25mmol / L, 15-40mmol / L, 10-20mmol / L, 5-15mmol / L, and 20-50mmol / L respectively; the surfactant is one of polyvinyl pyrrolidone, polysorbate, hexadecyltrimethylammonium bromide, and hexamethylenetetramine, and the mass concentration in the mixed solution is 2-15g / L; the metal chelating agent is one of ethylenediaminetetraacetic acid, disodium nitrilotriacetate, citric acid, gluconic acid, and sodium tripolyphosphate, and the molar concentration in the mixed solution is 5-35mmol / L; the organic solvent is one of ethylene glycol, n-propanol, glycerol, and isoamyl alcohol;

[0026] Step S2: immersing 2-6 parts by mass of graphite felt in 300-600 parts by mass of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment. After the treatment, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material; the microwave heat treatment power setting range is 100-500W, the temperature is 150-200°C, and the time is 20-80min;

[0027] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under the protection of an inert gas, and obtaining a niobium-bismuth-based high-entropy alloy modified electrode after naturally cooling to room temperature; the high-temperature heat treatment temperature is 800-1100° C., the time is 2-6 hours, and the inert gas is one of nitrogen, argon and helium.

[0028] Embodiment 1: This embodiment comprises the following steps:

[0029] Step S1: dissolving niobium oxalate, bismuth subsalicylate, cobalt nitrate, manganese citrate, nickel 2-ethylhexanoate, vanadium acetylacetonate, tungsten hexacarbonyl, hexadecyltrimethylammonium bromide and sodium tripolyphosphate in a n-propanol solution to obtain a mixed solution, wherein the molar concentrations of niobium oxalate, bismuth subsalicylate, cobalt nitrate, manganese citrate, nickel 2-ethylhexanoate, vanadium acetylacetonate and tungsten hexacarbonyl in the mixed solution are 50 mmol / L, 100 mmol / L, 25 mmol / L, 20 mmol / L, 15 mmol / L, 5 mmol / L and 20 mmol / L, respectively, the mass concentration of hexadecyltrimethylammonium bromide in the mixed solution is 2 g / L, and the molar concentration of sodium tripolyphosphate in the mixed solution is 5 mmol / L;

[0030] Step S2: immersing 4 g of graphite felt in 300 g of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment, wherein the microwave heat treatment power is 100 W, the microwave heat treatment temperature is 200° C., and the microwave heat treatment time is 40 min. After the end, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material;

[0031] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling material to high-temperature heat treatment under argon protection, wherein the high-temperature heat treatment temperature is 800° C. and the high-temperature heat treatment time is 4 hours, and after naturally cooling to room temperature, a niobium-bismuth-based high-entropy alloy modified electrode is obtained;

[0032] like Figure 2 As shown, the element distribution diagram of the niobium-bismuth-based high-entropy alloy modified electrode prepared in Example 1 clearly shows that a variety of elements are uniformly dispersed in the high-entropy alloy particles, indicating the uniformity and dispersibility of the metal distribution, which helps to enhance the electronic conduction ability of the modified electrode, thereby improving the voltage efficiency and energy efficiency. Figure 3 The energy efficiency curve of the battery assembled with electrodes prepared in Example 1 and Comparative Example 5 after 20 cycles shows that Example 1 exhibits higher energy efficiency, which is mainly due to the synergistic effect of various metal elements in the high entropy alloy, among which niobium element promotes the redox reaction of vanadium ions, bismuth element inhibits the hydrogen evolution side reaction at the cathode of the vanadium battery, and the addition of cobalt, manganese, nickel, vanadium and tungsten elements can promote the conductivity of the electrode, thereby effectively improving the performance of the all-vanadium liquid flow battery.

[0033] Embodiment 2: This embodiment comprises the following steps:

[0034] Step S1: dissolving niobium carbide, bismuth nitrate, cobalt acetate, manganese carbonate, nickel citrate, vanadyl sulfate, ammonium tungstate, polysorbate and ethylenediaminetetraacetic acid in a glycerol solution to obtain a mixed solution, wherein the molar concentrations of niobium carbide, bismuth nitrate, cobalt acetate, manganese carbonate, nickel citrate, vanadyl sulfate and ammonium tungstate in the mixed solution are 60, 80, 20, 30, 10, 15 and 30 mmol / L respectively, the mass concentration of polysorbate in the mixed solution is 6 g / L, and the molar concentration of ethylenediaminetetraacetic acid in the mixed solution is 5 mmol / L;

[0035] Step S2: immersing 6 g of graphite felt in 400 g of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment, wherein the microwave heat treatment power is 200 W, the microwave heat treatment temperature is 180° C., and the microwave heat treatment time is 60 min. After the end, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material;

[0036] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under nitrogen protection, wherein the high-temperature heat treatment temperature is 900° C. and the high-temperature heat treatment time is 6 hours. After naturally cooling to room temperature, a niobium-bismuth-based high-entropy alloy modified electrode is obtained.

[0037] Embodiment 3: This embodiment comprises the following steps:

[0038] Step S1: dissolving niobium chloride, bismuth sulfate, cobalt oxalate, manganese nitrate, nickel chloride, vanadium phthalocyanine, tungsten isopropoxide, polyvinyl pyrrolidone and citric acid in an isoamyl alcohol solution to obtain a mixed solution, wherein the molar concentrations of niobium chloride, bismuth sulfate, cobalt oxalate, manganese nitrate, nickel chloride, vanadium phthalocyanine and tungsten isopropoxide in the mixed solution are 60, 60, 15, 40, 15, 10 and 40 mmol / L respectively, the mass concentration of polyvinyl pyrrolidone in the mixed solution is 8 g / L, and the molar concentration of citric acid in the mixed solution is 25 mmol / L;

[0039] Step S2: immersing 2 g of graphite felt in 300 g of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment, wherein the microwave heat treatment power is 300 W, the microwave heat treatment temperature is 160° C., and the microwave heat treatment time is 80 min. After the end, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material;

[0040] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under helium protection, wherein the high-temperature heat treatment temperature is 1000° C. and the high-temperature heat treatment time is 5 hours. After naturally cooling to room temperature, a niobium-bismuth-based high-entropy alloy modified electrode is obtained.

[0041] Embodiment 4: This embodiment comprises the following steps:

[0042] Step S1: dissolving niobium oxalate, bismuth 2-ethylhexanoate, cobalt gluconate, manganese naphthenate, nickel citrate, ammonium metavanadate, ammonium tungstate, cyclohexamethylenetetramine and disodium nitrilotriacetate in an ethylene glycol solution to obtain a mixed solution, wherein the molar concentrations of niobium oxalate, bismuth 2-ethylhexanoate, cobalt gluconate, manganese naphthenate, nickel citrate, ammonium metavanadate and ammonium tungstate in the mixed solution are 80, 40, 10, 15, 12, 8 and 50 mmol / L respectively, the mass concentration of cyclohexamethylenetetramine in the mixed solution is 2 g / L, and the molar concentration of disodium nitrilotriacetate in the mixed solution is 35 mmol / L;

[0043] Step S2: immersing 5 g of graphite felt in 600 g of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment, wherein the microwave heat treatment power is 400 W, the microwave heat treatment temperature is 150° C., and the microwave heat treatment time is 50 min. After the end, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material;

[0044] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under nitrogen protection, wherein the high-temperature heat treatment temperature is 1100° C. and the high-temperature heat treatment time is 3 h. After naturally cooling to room temperature, a niobium-bismuth-based high-entropy alloy modified electrode is obtained.

[0045] Embodiment 5: This embodiment comprises the following steps:

[0046] Step S1: dissolving niobium chloride, bismuth nitrate, cobalt nitrate, manganese citrate, nickel 2-ethylhexanoate, vanadium acetylacetonate, tungsten isopropoxide, polysorbate and gluconic acid in an ethylene glycol solution to obtain a mixed solution, wherein the molar concentrations of niobium chloride, bismuth nitrate, cobalt nitrate, manganese citrate, nickel 2-ethylhexanoate, vanadium acetylacetonate and tungsten isopropoxide in the mixed solution are 70, 50, 10, 25, 20, 15 and 50 mmol / L respectively, the mass concentration of polysorbate in the mixed solution is 15 g / L, and the molar concentration of gluconic acid in the mixed solution is 20 mmol / L;

[0047] Step S2: immersing 3 g of graphite felt in 500 g of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment, wherein the microwave heat treatment power is 500 W, the microwave heat treatment temperature is 170° C., and the microwave heat treatment time is 20 min. After the end, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material;

[0048] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under argon protection, wherein the high-temperature heat treatment temperature is 900° C. and the high-temperature heat treatment time is 2 h. After naturally cooling to room temperature, a niobium-bismuth-based high-entropy alloy modified electrode is obtained.

[0049] Comparative Example 1: This embodiment includes the following steps:

[0050] Step S1: dissolving bismuth subsalicylate, cobalt nitrate, manganese citrate, nickel 2-ethylhexanoate, vanadium acetylacetonate, tungsten hexacarbonyl, hexadecyltrimethylammonium bromide and sodium tripolyphosphate in a n-propanol solution to obtain a mixed solution, wherein the molar concentrations of bismuth subsalicylate, cobalt nitrate, manganese citrate, nickel 2-ethylhexanoate, vanadium acetylacetonate and tungsten hexacarbonyl in the mixed solution are 50, 100, 25, 20, 15, 5 and 20 mmol / L respectively, the mass concentration of hexadecyltrimethylammonium bromide in the mixed solution is 2 g / L, and the molar concentration of sodium tripolyphosphate in the mixed solution is 5 mmol / L;

[0051] Step S2: immersing 4 g of graphite felt in 300 mL of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment, wherein the microwave heat treatment power is 100 W, the microwave heat treatment temperature is 200° C., and the microwave heat treatment time is 40 min. After the end, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material;

[0052] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under argon protection, wherein the high-temperature heat treatment temperature is 800° C. and the high-temperature heat treatment time is 4 hours. After naturally cooling to room temperature, a niobium-bismuth-based high-entropy alloy modified electrode is obtained.

[0053] Comparative Example 2: This embodiment includes the following steps:

[0054] Step S1: dissolving niobium oxalate, cobalt nitrate, manganese citrate, nickel 2-ethylhexanoate, vanadium acetylacetonate, tungsten hexacarbonyl, hexadecyltrimethylammonium bromide and sodium tripolyphosphate in a n-propanol solution to obtain a mixed solution, wherein the molar concentrations of niobium oxalate, cobalt nitrate, manganese citrate, nickel 2-ethylhexanoate, vanadium acetylacetonate and tungsten hexacarbonyl in the mixed solution are 50, 100, 25, 20, 15, 5 and 20 mmol / L respectively, the mass concentration of hexadecyltrimethylammonium bromide in the mixed solution is 2 g / L, and the molar concentration of sodium tripolyphosphate in the mixed solution is 5 mmol / L;

[0055] Step S2: immersing 4 g of graphite felt in 300 mL of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment, wherein the microwave heat treatment power is 100 W, the microwave heat treatment temperature is 200° C., and the microwave heat treatment time is 40 min. After the end, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material;

[0056] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under argon protection, wherein the high-temperature heat treatment temperature is 800° C. and the high-temperature heat treatment time is 4 hours. After naturally cooling to room temperature, a niobium-bismuth-based high-entropy alloy modified electrode is obtained.

[0057] Comparative Example 3: This embodiment includes the following steps:

[0058] Step S1: dissolving niobium oxalate, bismuth subsalicylate, hexadecyltrimethylammonium bromide and sodium tripolyphosphate in a n-propanol solution to obtain a mixed solution, wherein the molar concentrations of niobium oxalate and bismuth subsalicylate in the mixed solution are 50 and 100 mmol / L, respectively, the mass concentration of hexadecyltrimethylammonium bromide in the mixed solution is 2 g / L, and the molar concentration of sodium tripolyphosphate in the mixed solution is 5 mmol / L;

[0059] Step S2: immersing 4 g of graphite felt in 300 g of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment, wherein the microwave heat treatment power is 100 W, the microwave heat treatment temperature is 200° C., and the microwave heat treatment time is 40 min. After the end, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material;

[0060] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under argon protection, wherein the high-temperature heat treatment temperature is 800° C. and the high-temperature heat treatment time is 4 hours. After naturally cooling to room temperature, a niobium-bismuth-based high-entropy alloy modified electrode is obtained.

[0061] Comparative Example 4: This embodiment includes the following steps:

[0062] Step S1: dissolving niobium oxalate, bismuth subsalicylate, cobalt nitrate, manganese citrate, nickel 2-ethylhexanoate, vanadium acetylacetonate, tungsten hexacarbonyl and cetyltrimethylammonium bromide in a n-propanol solution to obtain a mixed solution, wherein the molar concentrations of niobium oxalate, bismuth subsalicylate, cobalt nitrate, manganese citrate, nickel 2-ethylhexanoate, vanadium acetylacetonate and tungsten hexacarbonyl in the mixed solution are 50, 100, 25, 20, 15, 5 and 20 mmol / L respectively, and the mass concentration of cetyltrimethylammonium bromide in the mixed solution is 2 g / L;

[0063] Step S2: immersing 4 g of graphite felt in 300 g of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment, wherein the microwave heat treatment power is 100 W, the microwave heat treatment temperature is 200° C., and the microwave heat treatment time is 40 min. After the end, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material;

[0064] Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under argon protection, wherein the high-temperature heat treatment temperature is 800° C. and the high-temperature heat treatment time is 4 hours. After naturally cooling to room temperature, a niobium-bismuth-based high-entropy alloy modified electrode is obtained.

[0065] Comparative Example 5: blank graphite felt.

[0066] Resistivity test method: Use a digital four-probe tester to test, cut the graphite felt into a size of 10cm×5cm, perform resistivity tests on 9 fixed positions, and take the average value to get the resistivity.

[0067] Battery test method: The niobium-bismuth-based high entropy alloy modified graphite felt electrodes obtained in Examples 1-5 and Comparative Examples 1-5 were assembled into a battery stack, and the battery charge and discharge performance test was performed under the same operating conditions, and the coulomb efficiency, voltage efficiency and energy efficiency were recorded. The test results are shown in the following table:

[0068] Table 1 Battery performance test table of battery stacks assembled using graphite felt from examples and comparative examples

[0069]

[0070] As can be seen from Table 1, compared with Comparative Example 1 and Comparative Example 5 (blank graphite felt), Examples 1-5 have more efficient energy efficiency and voltage efficiency. It can be seen that the addition of niobium elements in the high entropy alloy can effectively improve the energy efficiency of the graphite felt electrode, which is mainly due to the addition of niobium elements can accelerate the valence state transition of vanadium ions, thereby effectively improving its related energy efficiency and voltage efficiency; Compared with Comparative Example 2, Examples 1-5 have higher coulombic efficiency and energy efficiency, which is mainly attributed to the inhibitory effect of bismuth elements on the cathode hydrogen evolution reaction, thereby improving the charge and discharge related performance, and improving its related energy efficiency and coulombic efficiency; Compared with Comparative Examples 3-4, Examples 1-5 and Comparative Example 1-2 have higher energy efficiency, voltage efficiency and lower resistivity, which is mainly attributed to the introduction of highly conductive metals such as Co, Mn, W, Ni, V and metal chelators, wherein the metal chelator can effectively promote the uniform dispersion of multiple metals, improve the conductivity and electron transmission capacity of the high entropy alloy electrode, thereby effectively reducing the resistivity of the electrode and improving the coulombic efficiency and energy efficiency of the battery.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery, characterized in that: At least the following steps are included: Step S1: dissolving a niobium source, a bismuth source, a cobalt source, a manganese source, a nickel source, a vanadium source, a tungsten source, a surfactant and a metal chelating agent in an organic solvent to obtain a mixed solution; Step S2: soaking 2-6 parts by mass of graphite felt in 300-600 parts by mass of the mixed solution, and then transferring it to a microwave reactor for microwave heat treatment. After the treatment, the graphite felt is naturally cooled to room temperature, and the graphite felt is taken out, and washed with deionized water and ethanol respectively, and then vacuum dried to obtain a graphite felt electrode modified with a niobium-bismuth-based multi-metal oxide coupling material; Step S3: subjecting the graphite felt electrode modified by the niobium-bismuth-based multi-metal oxide coupling compound to high-temperature heat treatment under the protection of an inert gas, and naturally cooling it to room temperature to obtain a niobium-bismuth-based high-entropy alloy modified electrode.

2. The method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery according to claim 1, characterized in that: In step S1, the niobium source is one of niobium carbide, niobium oxalate and niobium chloride; the bismuth source is one of bismuth sulfate, bismuth 2-ethylhexanoate, bismuth subsalicylate and bismuth nitrate; the cobalt source is one of cobalt acetate, cobalt oxalate, cobalt nitrate and cobalt gluconate; the manganese source is one of manganese carbonate, manganese nitrate, manganese citrate and manganese cyclohexaneate; the nickel source is one of nickel chloride, nickel 2-ethylhexanoate and nickel citrate hydrate; the vanadium source is one of ammonium metavanadate, vanadium acetylacetonate, vanadium sulfate hydrate and vanadium phthalocyanine; the tungsten source is one of ammonium tungstate, tungsten hexacarbonyl and tungsten isopropoxide.

3. The method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery according to claim 1, characterized in that: In step S1, the molar concentrations of the niobium source, bismuth source, cobalt source, manganese source, nickel source, vanadium source and tungsten source in the mixed solution are 50-80 mmol / L, 40-100 mmol / L, 10-25 mmol / L, 15-40 mmol / L, 10-20 mmol / L, 5-15 mmol / L and 20-50 mmol / L respectively.

4. The method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery according to claim 1, characterized in that: In step S1, the surfactant is one of polyvinyl pyrrolidone, polysorbate, hexadecyltrimethylammonium bromide and hexamethylenetetramine, and the mass concentration of the surfactant in the mixed solution is 2-15 g / L.

5. The method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery according to claim 1, characterized in that: In step S1, the metal chelating agent is one of ethylenediaminetetraacetic acid, disodium nitrilotriacetate, citric acid, gluconic acid and sodium tripolyphosphate, and the molar concentration in the mixed solution is 5-35 mmol / L.

6. The method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery according to claim 1, characterized in that: The organic solvent in step S1 is one of ethylene glycol, n-propanol, glycerol and isoamyl alcohol.

7. The method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery according to claim 1, characterized in that: In step S2, the microwave heat treatment power is 100-500W, the temperature is 150-200°C, and the time is 20-80min.

8. The method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery according to claim 1, characterized in that: In step S3, the high temperature heat treatment temperature is 800-1100° C., the time is 2-6 hours, and the inert gas is one of nitrogen, argon and helium.

9. A niobium-bismuth-based high-entropy alloy modified electrode for vanadium battery, characterized in that: The electrode is prepared by the method for preparing a niobium-bismuth-based high-entropy alloy modified electrode for a vanadium battery as described in claims 1 to 8.

Citation Information

Patent Citations

  • Quick and effective modification method of graphite felt for vanadium battery

    CN108054390A

  • Electrochemical modification method of vanadium battery graphite felt electrode material

    CN111740127A